Hypertension, use of antihypertensive medications, and risk of epithelial ovarian cancer. Issue 2 (25th March 2016) - Huang, Tianyi; Poole, Elizabeth M.; Eliassen, A. Heather; Okereke, Olivia I.; Kubzansky, Laura D.; Sood, Anil K.; Forman, John P.; Tworoger, Shelley S.
Abstract : Few studies have examined the associations of hypertension and antihypertensive medications with ovarian cancer. In particular, beta‐blockers, one of the most commonly prescribed medications to treat hypertension, may reduce ovarian cancer risk by inhibiting beta‐adrenergic signaling. We prospectively followed 90, 384 women in the Nurses' Health Study (NHS) between 1988–2012 and 113, 121 NHSII participants between 1989–2011. Hypertension and use of antihypertensive medications were self‐reported biennially. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). We documented 948 ovarian cancer cases during follow‐up. Similar results were observed in the two cohorts. While hypertension was not associated with ovarian cancer risk (Pooled HR = 1.01; 95% CI = 0.88, 1.16), current use of any antihypertensive medication was associated with slightly increased risk compared to never users (Pooled HR = 1.18; 95% CI: 1.02, 1.37). This increased risk was primarily due to use of thiazide diuretics (Pooled HR = 1.37; 95% CI: 1.13, 1.68). No associations were observed for beta‐blockers or angiotensin‐converting‐enzyme inhibitors. Calcium channel blockers (CCBs) were associated with suggestively reduced risk (NHS HR = 0.73; 95% CI: 0.53, 1.01), after adjusting for all antihypertensive medications. Associations were similar among hypertensive women and stronger for longer use of thiazide diuretics and CCBs. In conclusion, our results provided no evidence that beta‐blockers were associated with reduced ovarian cancer risk. In contrast, we observed an increased risk for use of thiazide diuretics that should be confirmed in other studies. Abstract : What's new? Antihypertensive drugs lower blood pressure by acting through various mechanisms, some of which may be relevant to cancer. Yet, despite widespread use of antihypertensive medications, whether the drugs impact cancer risk remains disputed. Here, in two large prospective U.S. cohorts, current and long‐term use of thiazide diuretics was associated with a significantly increased risk of ovarian cancer. By contrast, no association was detected between ovarian cancer risk and hypertension, nor was an association observed for beta‐blockers, which have been shown experimentally to inhibit ovarian tumor growth. The findings could have important implications for ovarian cancer prevention.